2020
DOI: 10.1002/mma.7096
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a discrete method for a time‐delayed reaction–diffusion epidemic model

Abstract: In this work, we propose a time‐delayed reaction–diffusion model to describe the propagation of infectious viral diseases like COVID‐19. The model is a two‐dimensional system of partial differential equations that describes the interactions between disjoint groups of a human population. More precisely, we assume that the population is conformed by individuals who are susceptible to the virus, subjects who have been exposed to the virus, members who are infected and show symptoms, asymptomatic infected individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It should be noted that there are some papers, see, e.g., [73,74], in which the models based on reaction-diffusion equations with time delays are suggested for describing epidemic processes. Actually, such types of models are natural extensions of the models based on ODEs with time delays (see, e.g., Chapter 10 in [1]).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are some papers, see, e.g., [73,74], in which the models based on reaction-diffusion equations with time delays are suggested for describing epidemic processes. Actually, such types of models are natural extensions of the models based on ODEs with time delays (see, e.g., Chapter 10 in [1]).…”
Section: Discussionmentioning
confidence: 99%
“…The reader should know that the ongoing and future works are in the aim of developing more complex models combining the reviewed types (2), ( 3), ( 4) and ( 5). We refer for instance to the following recent works Khan, Ikram, Din, Humphries & Akgul (2021), Macías-Díaz et al (2020), Chinnathambi et al (2019), Ge & Chen (2021). Knowing all these types, it can be concluded that, while modeling a disease, the pertinence of the chosen model is indeed based on its capacity of maximizing the interpretation of reality but also on its ability to minimize the difficulty of the required mathematical and numerical tools for its analysis.…”
Section: Discussionmentioning
confidence: 99%